A prospective study on the role of Hysterolaparoscopy in the evaluation of infertility - B., Pandeeswari; Valecha, Shalini Mahana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Infertility affects about 10-15% of couples of reproductive age groups. The current evidence indicates a 9% prevalence of infertility with 56% of couples seeking medical care. Hysterolaparoscopy provides a comprehensive investigative procedure in which various factors causing female infertility can be assessed at one sitting. Methods: A total 100 infertile women between 20-40 years of age including primary and secondary infertility were evaluated. Patients would be investigated thoroughly for infertility and in preparation for anaesthesia. Tests include follicular study, Ultrasound pelvis. Hysterolaparoscopy was performed in the pre ovulatory period between days 6-10 of the cycle for infertility evaluation. Results: In the present study out of 100 cases for infertility evaluated, primary infertility were 57(57%) and secondary infertility were 43(43%). In our study out of 100 patients, Hysterolaparoscopy showed tuberculosis in 24 (24%) patients, remaining were endometriosis, polycystic ovarian syndrome, congestion, intra-pelvic adhesions, hydro-salpinx. Conclusions: It is concluded that while treating the causes of female infertility combined simultaneous diagnostic laparoscopy and hysteroscopy should be performed in all infertile patients as” seeing is believing” and if any pathologies found to be operable the gynaecologist can perform operative hystero-laparoscopy at that time, hence anticipating the pathologies after pre-operative work up is very important.